2020
DOI: 10.14434/jotlt.v9i1.29169
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student Success by Incorporating Instant-Feedback Questions and Increased Proctoring in Online Science and Mathematics Courses

Abstract: Introductory courses in mathematics and the physical sciences are challenging for students and often have lower success rates than other comparable courses.  In online courses, this problem is magnified given the greater propensity for students to engage in surface learning strategies.  In particular, it has been shown that students are not actively utilizing learning materials provided in the structured course modules such as lecture videos.  To combat this problem, we have implemented two different solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Woldeab and Brothen (2019) conducted a survey amongst 631 students and found that high test anxiety led to lower exam scores, especially in an online proctored setting. Law et al (2020) found online proctoring led to greater engagement with course materials and improved exam performance, but formative assessments remained consistent. Reisenwitz (2020) study supports the use of proctored online exams to fairly assess student performance.…”
Section: Category 2: Stakeholders' Concerns Of Using Digital Proctoringmentioning
confidence: 89%
“…Woldeab and Brothen (2019) conducted a survey amongst 631 students and found that high test anxiety led to lower exam scores, especially in an online proctored setting. Law et al (2020) found online proctoring led to greater engagement with course materials and improved exam performance, but formative assessments remained consistent. Reisenwitz (2020) study supports the use of proctored online exams to fairly assess student performance.…”
Section: Category 2: Stakeholders' Concerns Of Using Digital Proctoringmentioning
confidence: 89%
“…If the intervention was prolonged and the number of respondents exceeded that of this particular study, the research's findings might be improved. Law et al (2020); Vo et al (2020) claim that advanced achievement gives weaker students an advantage by having them study information at the basic level (Almasseri & AlHojailan, 2019). However, learning knowledge in economics has a larger cognitive load and requires higher-order thinking than other course content (Davis, 2015;Davis & Frederick, 2020;Hultberg & Calonge, 2017;Ping, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, Climant did not notice that this strategy could have made a difference in terms of student engagement until Deborah tried it. It worked-some of the students that were verbally silent during the lectures could still participate in the chatbox and respond to contributions from those that are verbally active, thus resulting in student-student engagement and instant feedback from the lecturer, which tends to improve students' achievement (Law, Tobin, Wilson, & Brandon, 2020). This illustrates that collectively we understood that a chatbox in Bb collaborates to engage students.…”
Section: Climantmentioning
confidence: 91%